ANALISIS RASIO INDIKATOR TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC PADA PT. BANK TABUNGAN NEGARA (BTN) TBK - MAULIDIYAH AGUSTINA, FIRDA (Jurnal Akuntansi AKUNESA, 2015)
ABSTRAKSI The aim of the research is to analyse the ratio indicator bank performance of Bank Tabungan Negara with using Risk Profile Governance Earnings and Capital (RGEC). This research using quantitative method. The research result using data financial report period 2011-2013. Ratio in this research is NPL, IRR, LR, ROA, NIM, and CAR. The result is overall performance Bank BTN is good at three years later and make Bank BTN include as category healthy bank in Indonesian with stabil condition. Keywords : RGEC, ratio indicator bank performance, Bank BTN